THE USE OF CODE MIXING BY NETIZEN IN THE COMMENTS COLUMN PREWEDDING PHOTO FLARES THAT CAUSED FIRE IN BROMO ON THE “PROBOLINGGOKITA” INSTAGRAM ACCOUNT - Nur Aini, Rofii’atul Fajriyah; Wafa, Hosnol; Tjahyadi, Indra; Andayani, Sri (Program Studi Bahasa Inggris, Universitas Panca Marga, 2024)
This research analyzes the phenomenon of code mixing in digital interaction in Indonesia, focusing on comments on the